5-Ureido-3, 3-diphenyl-3H-naphtho[2, 1-b]pyrans: Photoswitchable self-assembling architectures. (2004) - Sallenave, X.; Delbaere, S.; Ahmed, S.; Vermeersch, G.; Pozzo, J. L.
Abstract : 5-Ureido-3, 3-diphenyl-3 H -naphtho[2, 1-b]pyrans have been synthesized and their photochromic properties have been quantified using UV-Visible spectroscopy. The urea pattern is responsive for the selfassembling properties under both colourless and coloured forms whereas the corresponding amino derivatives do not show any aggregative properties. The geometries of the different states have been assigned using 1 H and 19 F NMR spectroscopies, and thereafter their respective kind of aggregates could be proposed through the different inter- and intramolecular interactions. Upon UV irradiation, the pyranic ring is opened and the resulting photogenerated carbonyl group is competing with the urea in the self-assembling process and consequently strongly affects the supramolecular assemblies. The inter- and intramolecular contributions have been quantified through 1D and 2D NMR experiments along with the variation in the concentration.